2014
DOI: 10.1186/bcr3684
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta receptor type III is a tumor promoter in mesenchymal-stem like triple negative breast cancer

Abstract: IntroductionThere is a major need to better understand the molecular basis of triple negative breast cancer (TNBC) in order to develop effective therapeutic strategies. Using gene expression data from 587 TNBC patients we previously identified six subtypes of the disease, among which a mesenchymal-stem like (MSL) subtype. The MSL subtype has significantly higher expression of the transforming growth factor beta (TGF-β) pathway-associated genes relative to other subtypes, including the TGF-β receptor type III (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…With regard to chromosome 1, the most frequent target was TGFBR3 , affected by breaks and/or loss of one copy in four cases and the JU‐PI cell line, and gain of one copy in one. TGFBR3 is a co‐factor in TGF beta signal transduction, and while some reports have suggested that it may have an oncogenic role in certain contexts, most data support a suppressor role in various carcinomas . The latter scenario could fit with the current results, but the expression of TGFBR3 was not lower in tumors with loss of one copy of the 5′‐end or of the entire gene.…”
Section: Discussionsupporting
confidence: 70%
“…With regard to chromosome 1, the most frequent target was TGFBR3 , affected by breaks and/or loss of one copy in four cases and the JU‐PI cell line, and gain of one copy in one. TGFBR3 is a co‐factor in TGF beta signal transduction, and while some reports have suggested that it may have an oncogenic role in certain contexts, most data support a suppressor role in various carcinomas . The latter scenario could fit with the current results, but the expression of TGFBR3 was not lower in tumors with loss of one copy of the 5′‐end or of the entire gene.…”
Section: Discussionsupporting
confidence: 70%
“…Mechanistically, T␤RIII regulates these pathways either by altering the actin cytoskeleton, via T␤RIII/␤-arrestin2 cytoplasmic interactions (24), or by GAG chain interactions with FGF2 (23). Overall, T␤RIII also acts as a tumor suppressor in prostate (19), lung (25), pancreatic (18), and breast cancer (16,21,26,27) but has been shown to promote metastasis in specific mesenchymal stem-like breast cancers (28), indicating its complex roles for T␤RIII in cancer.…”
mentioning
confidence: 99%
“…Higher levels of EMT genes under EpiC as compared to CRC conditions paralleled previous reports of EpiC cultured cells undergoing EMT (Nakles et al, 2013) in comparison to retention of cuboidal architecture (Saenz et al) and suppression of the EMT-related TGFB pathway (Ligaba et al, 2015) under CRC conditions. Here we documented upregulated TGFBR3 expression, a protein linked to a subtype of triple negative breast cancers in women (Jovanović et al, 2014), under EpiC conditions. Provocatively we found the TFBS for ZEB1, an EMT-linked gene, enriched in CRC-associated DEGs.…”
Section: Discussionmentioning
confidence: 87%
“…The same spectrum of histopathology is found in human triple negative breast cancers (Lehmann et al, 2011). One of the human mesenchymal-stem like (MSL) triple negative histologies demonstrates TGFBR3 over-expression (Jovanović et al, 2014). …”
Section: Introductionmentioning
confidence: 99%